Efficacy and safety of direct oral anticoagulant therapy for the treatment of venous thromboembolism in patients with chronic liver disease. Issue 176 (April 2019) - Davis, Kyle A.; Puleo, Charles R.; Kovalic, Alexander J.; Nisly, Sarah A.
Highlights: The efficacy and safety of direct oral anticoagulants in patients with chronic liver disease has not been well established. In a retrospective cohort study we aimed to evaluate direct oral anticoagulants for the treatment of VTE in this population. Patients with severe liver disease were more likely to receive warfarin. Patients receiving DOAC therapy had a similar rate of recurrent VTE and major bleeding as warfarin patients at 3 months. DOAC therapy may provide an alternative to warfarin in patients with chronic liver disease.